Identification of rye B chromosome-associated peptides by mass spectrometry - Ma, Wei; Liu, Zhao Jun; Sebastian, Beier; Houben, Andreas; Carpentier, Sebastien C. (Wiley, 2021)
B chromosomes (Bs) are supernumerary dispensable components of the standard genome (A chromosomes, As) that have been found in many eukaryotes. So far, it is unkown whether the B‐derived transcripts translate to proteins or if the host proteome is changed due to the presence of Bs. Comparative mass spectrometry was performed using the protein samples isolated from shoots of rye plants with and without Bs. We aimed to identify B‐associated peptides and analyzed the effects of Bs on the total proteome. Our comparative proteome analysis demonstrates that the presence of rye Bs affects the total proteome including different biological function processes. We found 319 of 16 776 quantified features in at least three out of five +B plants but not in 0B plants; 31 of 319 features were identified as B‐associated peptide features. According to our data mining, one B‐specific protein fragment showed similarity to a glycine‐rich RNA binding protein which differed from its A‐paralogue by two amino acid insertions. Our result represents a milestone in B chromosome research, because this is the first report to demonstrate the existence of Bs changing the proteome of the host.B chromosomes (Bs) are supernumerary dispensable components of the standard genome (A chromosomes, As) that have been found in many eukaryotes. So far, it is unkown whether the B‐derived transcripts translate to proteins or if the host proteome is changed due to the presence of Bs.Comparative mass spectrometry was performed using the protein samples isolated from shoots of rye plants with and without Bs. We aimed to identify B‐associated peptides and analyzed the effects of Bs on the total proteome.Our comparative proteome analysis demonstrates that the presence of rye Bs affects the total proteome including different biological function processes. We found 319 of 16 776 quantified features in at least three out of five +B plants but not in 0B plants; 31 of 319 features were identified as B‐associated peptide features. According to our data mining, one B‐specific protein fragment showed similarity to a glycine‐rich RNA binding protein which differed from its A‐paralogue by two amino acid insertions.Our result represents a milestone in B chromosome research, because this is the first report to demonstrate the existence of Bs changing the proteome of the host.